Whiplash Makulopatinin Akut Evre Optik Koherens Tomografi Bulguları - (:unkn) unknown (My University, 2019)
Başın savrulmasına sebep olmuş araç içi trafi k kazası sonrası her iki gözde görmede azalma ve merkezi görmede bozulma şikayeti ile başvuran52 yaşında erkek hastanın optik koherens tomografi sinde (OKT) her iki tarafl ı foveal pitin ve iç retina mimarisinin korunduğu yaygın makülerödem, dış retinal segmentte kalınlaşma ve subretinal sıvı mevcuttu. Kazayı takip eden 2 haftada nonsteroid antiinfl amatuar tedavi ile ödemkademeli olarak çözüldü, görsel iyileşme sağlandı. 3. ay sonunda hastanın her iki gözde görme keskinliği tam, OKT’ de tüm retina anatomisinormaldi. Whiplash yaralanmaları trafi k kazaları sonrası sık görülmesine rağmen, isimlendirmeden dolayı whiplash makülopati tanısı litera-türde çok az olguda tanımlanmıştır. Hastalar görme azalması ve merkezi görmede bozulmadan şikayet eder. Literatürde retina değişikliklerininkendiliğinden emilebileceği bildirilmiştir. Bizim olgumuzda bu patolojiyi açıkça göstermekle birlikte topikal nonstreoid antiinfl amatuar tedaviile bulguları gerilemiştir.

After the car accident with whiplash injury, a 52 year old male patient had reduction in visual acuity and loss of central vision. There were bilateral intraretinal edema and subretinal fl uid in optical coherent tomography (OCT). OCT fi ndings included a thickened outer retina. The architecture of the inner retina and the foveal pit were preserved. During 2 weeks following the accident, topical nonsteroid antiinfl ammatory treatment solved the edema gradually and visual recovery was achieved. At the end of the third month, the patient’s bilateral visual acuity was 20/20 , and the entire retinal anatomy was normal in OCT. Although whiplash injuries often occur after traffi c accidents, whiplash macu- lopathy is very rarely described in the literature because of its naming. Patients complain about decreased vision and central scotoma. It has been reported that these retinal changes can be absorbed spontaneously. In our case; similar to previous publications, the pathology is clearly demonstrated. Apart from the others in our case fi ndings recovered with the use of topical NSAI.
Optical Coherence Tomography Findings of Whiplash Maculopathy
Keywords: Göz Hastalıkları